Praktik Pembuatan “Sate Tegeh” sebagai Jalan Pemahaman Makna dan Upaya Pelestarian Unsur Ritual di Desa Pakraman Padang Luwih, Canggu, Badung - I Wayan Watra (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
The sate tegeh (high skewer) offering is an essential element in the yadnya ceremony in Bali, but one who can make sate tegeh is only limited to the older generation who pursue it. This article explores the practice of making sate tegeh for community members in Pakraman Village Padang Luwih, Canggu, Badung Regency. In addition to analyzing the practice of making sate tegeh, this article also discusses the functions and philosophy of satay tegeh based on traditional Balinese values ??and traditions. Data were collected by observation, interview and document review techniques. Data analyzed with symbol theory by examining the form and meaning of sate tegeh elements in Balinese customs and traditions. The results showed that the practice of making satay tegeh was not only related to skills, but also as a medium for the deepening of the teachings and ritual philosophy of sate tegeh. It is recommended that villages in Bali regularly carry out work practices to make sate tegeh so that this traditions can be preserved.